NOVEL APPROACHES FOR THE DETERMINATION OF BIOGENIC AMINES IN FOOD SAMPLES - RIVOIRA, Luca; ZORZ, Mojca; MARTELANC, Mitja; BUDAL, Sara; CARENA, Davide; FRANKO, Mladen; BRUZZONITI, Maria Concetta (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Wine is a fermented beverage that could be affected by high concentrations of biogenic amines which alter organoleptic properties. In this work, new analytical approaches for determination of biogenic amines in wines were developed. For the first time, we studied the derivatization of BAs in wines with naphthalene-2,3-dicarboxaldehyde (NDA) and with dabsyl chloride (DBS) and analysis of derivatized Bas by HPLC coupled to fluorescence (HPLC-NDA-FL) and thermal lens spectrometry (HPLC-DBS-TLS) detectors. The sensitivity of the two methods (LODs HPLC-NDA-FL in the range 27-73 µg/L; LODs HPLC-DBS-TLS in the range 3.4-11 µg/L) was higher than that of the official method for biogenic amines in wines, OIV-MA-AS315-18 (60-77 µg/L). For its best performances, the HPLC-DBS-TLS technique was applied to the analysis of putrescine, cadaverine, histamine and tyramine in two white wine samples. Additionally, exploiting the Berthelot reaction, the TLS fast screening of biogenic amines in wines, following the release of ammonia by transglutaminase, was also proposed. This approach allowed us to determine total biogenic amount content in concentrations below 0.1 mg/L, expressed as equivalents of histamine.